2021
DOI: 10.1186/s13002-021-00480-x
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of ethnomedicinal plants and their practices in human and livestock healthcare in Haripur District, Khyber Pakhtunkhwa, Pakistan

Abstract: Background The utilization of plants and plant resources for various ethnobotanical purposes is a common practice in local towns and villages of developing countries, especially in regard to human and veterinary healthcare. For this reason, it is important to unveil and document ethnomedicinal plants and their traditional/folk usage for human and livestock healthcare from unexplored areas. Here we advance our findings on ethnomedicinal plants from Haripur District, Pakistan, not only for conser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…This ethnic knowledge is inextricably tied to the local biodiversity and has been woven into the rural communities' fabric for centuries. Consequently, herbal treatments are to the indigenous Himalayan therapeutic practices ( 9 , 10 ). The documentation of this altruistic folk knowledge is essential now that the Nagoya Protocol has been ratified to preserve cultural heritage ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…This ethnic knowledge is inextricably tied to the local biodiversity and has been woven into the rural communities' fabric for centuries. Consequently, herbal treatments are to the indigenous Himalayan therapeutic practices ( 9 , 10 ). The documentation of this altruistic folk knowledge is essential now that the Nagoya Protocol has been ratified to preserve cultural heritage ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…Khan, Khan, et al (2015) reported 13 similar species; ul Hassan et al (2014) reported 7 similar species, Tariq et al (2015) reported 6 similar species and Raziq et al (2010) reported 5 similar species from different locations of Pakistan with the same ethnoveterinary uses. Several studies have reported similar ethnoveterinary uses of certain plants such as Chenopodium ambrosioides, Zea mays, Acacia modesta, Avena sativa, Malva neglecta, Saccharum officinarum, Convolvulus arvensis and Acacia nilotica (Akerreta et al, 2010; Giday & Teklehaymanot, 2013; Lans et al, 2007; Maphosa & Masika, 2010; Martinez & Lujan, 2011; Shen et al, 2010). According to Vogl et al (2016), farmers in Eastern Tyrol (Austria) have extensive knowledge of fodder species and their applications for livestock health.…”
Section: Discussionmentioning
confidence: 97%
“…Ethnoveterinary medicines are part of the ecosystem that uses folk beliefs, traditional knowledge and practices to maintain animal health and cure diseases (Mathias-Mund & McCorkle, 1989). More than 80% of the world's population uses herbal products and plants as a source of health care, either directly or indirectly (Siddique et al, 2021). Pakistan is an agricultural country, with agriculture and livestock supporting approximately 80% of the population (Rehman et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Where: UVis = the use values of the species s mentioned by the informants i; ∑Uis = the number of uses of species s mentioned in each event by the informants i; nis = the number of events in which the informants i cited species s (Siddique et al 2021).…”
Section: Use Value (Uvis) = (∑Uis)⁄nismentioning
confidence: 99%